KEEFEKTIFAN MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TERHADAP KEMAMPUAN MENULIS EKSPOSISI BERITA PADA SISWA KELAS V SDI NO 21 SALOMONI KABUPATEN BARRU - Asrianti Asrianti; Munirah Munirah (Universitas Pakuan, 2021)
THE EFFECTIVENESS OF COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) LEARNING MODELS ON EXPOSITION WRITING ABILITY NEWS ON STUDENTS OF CLASS V SDI NO 21 BARRU DISTRICT SALOMONIThis study aims to examine the effectiveness of cooperative integrated reading and composition (CIRC) learning model on the ability to write news expositions in grade V students of SDI No. 21 Salomoni Barru Regency. The type of research used in this research is experimental research. The research design used, namely quasi experiment form Pretest-Posttest Control Group Design. This research was conducted in SDI No. 21 Salomoni Barru Regency. The population, namely the entire Va. and VB students of 42 students. Sampling techniques, namely saturated sampling. The instrument used in this research is the task of writing simple sentences with data collection techniques, namely the assignment. The collected data is then analyzed using descriptive statistics and inferential statistics.The results showed that the ability to write news exposition using Cooperative Integrated Reading and Composition (CIRC) learning in grade V students of SDI No. 21 Salomoni Barru District showed that students' understanding of writing news exposition texts showed an increase in the 9 students whose initial pretest implementation was still in the good category. While the ability to write news exposition without using Cooperative Integrated Reading and Composition (CIRC) learning in grade V students of SDI No. 21 Salomoni Barru District from 22 students who participated in pretest before learning there were 12 students (54.5%) who have the ability to write news exposition texts that are in a very good categor. Furthermore, as many as 10 students (45.5%) who have the ability to write news exposition texts that are in a good categor. The results showed that in the implementation of pretest students the ability of students in writing news exposition texts is classified as effective. While in the posttest implementation after the implementation of CIRC learning obtained that the grades obtained by students are in the category of very effective. Thus, the implementation of learning using CIRC learning based on posttest results is declared effective.